The Urartian Onomasticon: A prosopographic study - Grekyan, Yervand (ARAMAZD: Armenian Journal of Near Eastern Studies, 2024)
The research of the Urartian anthroponyms has a long history, with its beginnings going back to the turn of the 19th century, but almost all scholars focused their attention on the study of royal or throne names of the Urartian kings. Only a few personal names have been investigated in the commentaries of the text editions in later studies. Seemingly, the limited linguistic material of the Urartian language recorded in texts, including hapax legomena and a large number of poorly- or non-interpretable words, has limited also the interest towards Urartian onomastics. Undoubtedly, the Urartian kingdom was a home of various ethnic groups. The multiethnic character of the state was further deepened by the Urartians themselves who employed a policy of large-scale deportations and planned resettlements. The introduction of several hundred thousand, if not a million deportees after the successful campaigns of the Urartian kings of the late-9th – first half of the 8th century BC, deeply changed the ethno-linguistic character of the state. The ethnic migrations that took place especially in the late 8th – 7th centuries BC made further contribution to this process resulting in the increasing role of the local or formerly deported populations in the life of Urartu in later stages of its existence. Hence, not all the names attested in the Urartian inscriptions or recorded in the Neo-Assyrian sources in connection with Urartian affairs belong to the Urartians. At the same time not all the Urartians bore Urartian or, generally speaking, Hurro-Urartian-related names. The same is true for individuals, who are not described as Urartians in the Neo-Assyrian contemporary sources, but their names clearly point to the Urartian cultural world. The present work is an attempt to investigate all available onomastic data directly or in some way related to Urartu and the Urartians and to present a prosopographic study. In order to widen the available comparative data, I tried to consider also the linguistic and onomastic material of the 2nd millennium BC, hence, the study is largely based on the cuneiform sources and the known vocabulary of the spoken languages of the period. First among these is Hurrian, a related language that shares a large number of related words with Urartian. The corpora of the Urartian cuneiform texts, now available also as an electronic text corpus, and the enormous ‘Prosopography’ of the Neo-Assyrian Empire serve as the main bases for the current work.